Development of Nanobodies Against Hemorrhagic and Myotoxic Components of Bothrops atrox Snake Venom - Bailon Calderon, Henri; Yaniro Coronel, Verónica Olga; Cáceres Rey, Omar Alberto; Colque Alave, Elizabeth Gaby; Leiva Duran, Walter Jhon; Padilla Rojas, Carlos; Montejo Arevalo, Harrison; García Neyra, David; Galarza Pérez, Marco; Bonilla, César; Tintaya, Benigno; Ricciardi, Giulia; et al. (Frontiers in Immunology, 2020)
Snake envenoming is a globally neglected public health problem. Antivenoms produced using animal hyperimmune plasma remain the standard therapy for snakebites. Although effective against systemic effects, conventional antivenoms have limited efficacy against local tissue damage. In addition, potential hypersensitivity reactions, high costs for animal maintenance, and difficulties in homogeneity from batch-to-batch, are some of the factors that have motivated the search for innovative and improved therapeutic products against such envenomings. In this study, we developed a set of nanobodies (recombinant single-domain antigen-binding fragments from camelid heavy chain-only antibodies) against Bothrops atrox snake venom hemorrhagic and myotoxic components. An immune library was constructed after immunizing a Lama glama with the whole venom of B. atrox, from which nanobodies were selected by phage display using partially purified hemorrhagic and myotoxic proteins. Biopanning selections retrieved 18 and 8 different nanobodies against the hemorrhagic and the myotoxic proteins, respectively. In vivo assays in mice showed that five nanobodies inhibited the hemorrhagic activity of the proteins, three of which neutralized the hemorrhagic activity of whole B. atrox venom, while four nanobodies inhibited the myotoxic protein. A mixture of the anti-hemorrhagic and anti-myotoxic nanobodies neutralized the local tissue hemorrhage and myonecrosis induced by the whole venom, although it failed to prevent its lethality. Our results demonstrate the efficacy and usefulness of these nanobodies to neutralize important pathological effects of the venom, highlighting their potential as innovative therapeutic agents against envenomings by B. atrox, a medically important viperid species in South America.